(untitled) (Global Journal of Human-Social Science, 2021)
Bangladesh s socioeconomic realities include the problem of child labor This is a huge problem that cannot be overlooked In this study I looked at the elements that contribute to child labor in Bangladesh Poverty is the primary cause of children working as child laborers The issue of child labor has become one of the most prominent challenges in developing countries To put an end to this societies and governments must act together The government in particular must ensure that citizens basic rights are protected Following that the implementation of child labor legislation and a social boycott of child work would be an effective remedy